Litterfall silicon flux in relation to vegetation differences in old‐growth and logged lowland forests in Borneo. Issue 5 (1st July 2021) - Nakamura, Ryosuke; Imai, Nobuo; Aoyagi, Ryota; Kitayama, Kanehiro; Kitajima, Kaoru
Abstract: Lowland tropical forests cycle large quantities of silicon (Si) via litterfall, but little is known how litterfall Si flux is modified in logged forests. In Sabah, Borneo, we compared an old‐growth forest stand and stands that had received reduced‐impact logging (RIL) or conventional logging (CL) about 20–30 years ago, in terms of Si concentration of recently abscised dead leaves, Si flux via litterfall, and water extractable Si from upper soil horizons. The Si concentration of dead leaves produced by dominant tree species in Dipterocarpaceae differed widely among genera and species (1.2–29.7 mg Si g‐dry‐mass −1 ). Some pioneer trees (e.g., Macaranga spp.) and bamboo species that dominate the RIL and CL stands exhibited high Si concentration in their dead leaves. Litterfall Si flux was higher in the RIL stand (392 kg ha −1 year −1 ) where bamboo was abundant, than in the CL and old‐growth stands (187 and 153 kg ha −1 year −1, respectively). Water extractable Si from the soil was also the highest in the RIL stand, followed by the CL and old‐growth stands. In conclusion, our study suggests that bamboos and pioneer trees with high dead‐leaf Si concentrations increase Si flux in post‐logging stands, in a manner to compensate for the loss of Si flux associated with decreased abundance of Si accumulating Dipterocarpaceae trees. The correlation between litterfall Si flux and water extractable soil Si among the three stands also suggests a feedback loop of Si via plants in this lowland tropical forest that received contrasting types of logging. Abstract : Lowland tropical forests cycle large quantities of silicon (Si) via litterfall, but little is known how litterfall Si flux is modified in logged forests. We report that differences in species composition and abundance that received contrasting types of logging modified aspects of ecosystem Si cycling in a lowland tropical forest.